The Teacher's Guide to Scratch - Beginners : Professional Development for Coding Education - Hutchence, Kai (Routledge, 2024)
"The Teacher's Guide to Scratch - Beginners is a practical guide for educators preparing beginners-level coding lessons and assignments in their K-12 classrooms. The world's largest and most active visual programming platform, Scratch helps today's schools answer the growing call to realize important learning outcomes using coding and computer science. This book illustrates the benefits and fundamental building blocks of Scratch coding, details effective pedagogical strategies and learner collaborations, and offers actionable, accessible troubleshooting tips. Geared toward the fledgling user, these four unique coding projects will provide the technical training that teachers need to feel comfortable and confident in their skills and to help instill the same feeling of accomplishment in their students. Clear goals, a comprehensive glossary, and other features ensure the project's enduring relevance as a reference work for computer science education in grade school. Thanks to Scratch's cost-effective open-source license, suitability for blended and project-based learning, notable lack of privacy or security risks, and consistency in format even amid software and interface updates, this will be an enduring practitioner manual and professional development resource for years to come"--